Analysis and Evaluation of Financial Liquidity of Companies with Low Market Value Listed on the Warsaw Stock Exchange - Kuciński, Andrzej (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis: The purpose of this article is to analyze and evaluate the liquidity of listed companies with low capitalization, whose market value did not exceed PLN 20 million. The study takes as a hypothesis that companies with low market value listed on the Main Market of the Warsaw Stock Exchange maintain low levels of financial liquidity ratios, which translate into a negative evaluation of financial liquidity. Methodology: The study covered companies listed on the Main Market of the Warsaw Stock Exchange, whose market value was less than PLN 20 million. The study covered the years 2018–2020. The study used classical tools applied in the evaluation of corporate liquidity: the current liquidity ratio, quick liquidity ratio and cash liquidity ratio, as well as tools of descriptive statistics. Results of the research: Based on the research, it was found that companies with small market capitalization listed on the Main Market of the Warsaw Stock Exchange maintain liquidity ratios that are often below theoretical values. This means that the activities of companies whose market value was less than PLN 20 million are accompanied by an increased solvency risk, which translates into a worse assessment of the financial situation of companies and their low market valuation. In addition, on the basis of the research conducted, it was shown that there is a large differentiation of financial liquidity by sector of companies.